Phytochemical Screening, Cytotoxic and Anthelmintic Activities of Amorphophallus campanulatus (Roxb.), Avicennia marina (Forssk.) and Launaea sarmentosa (Willd.) (Bangladesh Pharmaceutical Journal, 2016)
Amorphophallus campanulatus (Roxb.), Avicennia marina (Forssk.) and Launaea sarmentosa (Willd.) are widely used plants in Asian folk and traditional medicines. In the present study, we have tried to find out the phytoconstituents, anthelmintic activity and cytotoxicity of the methanolic extracts of these plants. Anthelmintic activity was assessed by recording paralysis and death time with different concentrations of the plant extracts; while brine shrimp lethality test (BSLT) method was used to evaluate the cytotoxicity of the proposed plant extracts, where vincristine sulphate was used as positive standard control. The plant extracts demonstrated positive response in the tests for alkaloids, carbohydrates, saponins, phytosterols, phenols, flavonoids and amino acids that have huge and diverse phytochemical values. Anthelmintic test showed that methanol extract of Avicennia marina at 40 mg/ml significantly caused paralysis and death of worms and the required time were found to be 19.0 ± 1.46 min and 32.67 ± 0.95 min, respectively which gradually increased with the decrease of concentration. A. campanulatus also showed minimum paralysis and death time of 24.66 ± 0.37 min and 38.33 ± 0.27 min, respectively while standard albendazole caused paralysis and death of worms after 35.33 ± 58 min and 71.33 ± 1.15 min of administration, respectively. In this test distilled water was used as negative control and no mortality of the worms was observed. In case of cytotoxicity measurement, the crude methanolic extract of A. campanulatus, A. marina and L. sarmentosa revealed positive result with LC50 values of 0.0005 ?g/ml, 1.345 ?g/ml and 5.652 ?g/ml, respectively as compared to standard vincristine sulphate (0.839 ?g/ml).Bangladesh Pharmaceutical Journal 19(1): 106-113, 2016